Ballistic properties of silicon carbide ceramic under weak support conditions - Jiawei Bao; Yangwei Wang; Xingwang Cheng; Fuchi Wang; Huanwu Cheng (Journal of Materials Research and Technology, 2024)
Ceramic materials play an important role in the composite armor structures used to defend against armor-piercing projectiles. Previous studies have focused on understanding ceramics' energy absorption and ballistic properties under strong constraints. Specifically, this research studied the ballistic properties of silicon carbide (SiC) ceramics under weak support conditions. Ballistic tests were performed to measure the resistance of SiC ceramics with different thicknesses against 7.62×54mmR armor-piercing (AP) projectiles under weak support conditions. The results were then simulated and analyzed using the LS-DYNA software. The study found that even under weak support conditions, the SiC ceramic has a higher ballistic efficiency than the 2024-T351 aluminum alloy. As the thickness of SiC increased from 3 mm to 15mm, the ceramic self-constraint effect on damaged parts was enhanced within ceramics, leading to an increase in energy dissipation during both the dwell and penetration phase, and more projectile kinetic energy transformed into the internal energy of the projectile and the energy of the ceramic. In particular, a 15 mm thick SiC ceramic can effectively defend against 7.62×54mmR AP projectiles. The study highlights the importance of considering the thickness and constraint effect of the ceramic itself when evaluating the ballistic properties of SiC ceramics with poor constraint conditions.